2010
DOI: 10.1016/j.juro.2009.12.056
|View full text |Cite
|
Sign up to set email alerts
|

[-2]Proenzyme Prostate Specific Antigen is More Accurate Than Total and Free Prostate Specific Antigen in Differentiating Prostate Cancer From Benign Disease in a Prospective Prostate Cancer Screening Study

Abstract: Purpose Due to the limited specificity of prostate-specific antigen (PSA) for prostate cancer (CaP) screening, there is an ongoing search for adjunctive biomarkers. Retrospective studies have suggested that an isoform of proenzyme PSA called [−2] proPSA (p2PSA) may enhance the specificity of PSA-based screening. The objective of our study was to examine the utility of p2PSA in a prospective CaP screening study. Materials and Methods From a population of 2034 men undergoing CaP screening, we examined the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
87
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(91 citation statements)
references
References 25 publications
(44 reference statements)
1
87
1
2
Order By: Relevance
“…Based on p2PSA, the 'Prostate Health Index' (PHI) has been developed (a formula that includes p2PSA, f-PSA and t-PSA) and PHI was shown to improve the diagnostic accuracy for prostate cancer [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Based on p2PSA, the 'Prostate Health Index' (PHI) has been developed (a formula that includes p2PSA, f-PSA and t-PSA) and PHI was shown to improve the diagnostic accuracy for prostate cancer [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…[43,44] ProPSA, and Prostate Health Index (PHI) It is a mathematical equation demonstrating probability of prostate cancer This equation is formulated as p2PSA/fPSA)/ [14] Higher PHI values have been associated with increased probability of prostate cancer. Le et al [45] performed ROC analyses, and demonstrated the highest performance for phi among other tumor markers with an AUC of 0.77. With a specificity of 33%, phi reached nearly 2-fold specificity of fPSA/tPSA.…”
Section: Human Kallikrein-2 (Hk2)mentioning
confidence: 99%
“…Sokoll et al have demonstrated that the ratio of 2pPSA to fPSA (%2pPSA) is capable of improving prostate cancer detection and is correlated with the risk of aggressive disease (13). Le et al have shown that the use of %2pPSA or the combination of 2pPSA, PSA and fPSA in the so-called 'prostate health index' (PHI) proved superior in discriminating between prostate cancer and benign disease in males with a total PSA of 2.5-10 ng/ml and negative digital rectal examination (14). These results have been confirmed in a recent multicenter study conducted in 892 subjects with PSA values between 2 and 10 ng/ml (15).…”
Section: Introductionmentioning
confidence: 99%